Multiscalar energy transitions: Exploring the strategies of renewable energy cooperatives in South Korea. (November 2021) - Park, Seona; Yun, Sun-Jin
Highlights: The multiscalar perspective provides deep insight into niche–regime interactions. Each scale—local, regional, and national—exerts institutional inertia. Niche actors creatively adjust subregimes at the local and regional scales. Policymakers need detailed strategies to break the inertia at each scale. Abstract: We investigate the multiscale roles of renewable energy cooperatives (RE co-ops) in South Korea. This paper focuses on citizen participatory RE co-ops as a niche that plays a vital role in the community-led energy pathway. This paper conducted a narrative analysis based on data about RE co-ops' current status and in-depth interviews. We analyzed core changes and inertia in the conventional energy system at the national, regional, and local scales by comparing within and between scales. Each scale consisted of a patchwork of distinguishable subregimes, i.e., market, policy, and culture. We argue that a niche plays the creative role of adjusting the subregimes at each scale grounded in manageable resources such as their economic means, bylaws, and relationships. By identifying a gap between the ideal community-led energy pathway and how each spatial scale works, we show that a strategic political process should fill the gap, especially when niche actors try to actualize energy transition under adverse conditions.